2017
DOI: 10.3892/etm.2017.5414
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydroxy safflower yellow A on coronary heart disease through Bcl‑2/Bax and PPAR‑γ

Abstract: Abstract. The aim of the present study was to investigate the effect of hydroxy safflower yellow A (HSYA) on coronary heart disease through assessing the expression of B-cell lymphoma 2 (Bcl-2)/Bcl-2-like protein 4 (Bax) and peroxisome proliferator-activated receptor (PPAR)-γ. Coronary heart disease was induced in male Bama miniature swines via thoracoscope to serve as an animal model. Coronary heart disease swine were lavaged with 20 or 40 mg/kg HSYA. The mRNA levels of tumor necrosis factor (TNF)-α, interleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…Exposing neutrophils or macrophages to HMGB1 can lead to enhanced NF-κB signaling pathway and pro-inflammatory cytokine expression (Park et al, 2004). Interestingly, SY can improve inflammatory response and exert effect on inflammatory factors, like TNF-α, IL-1(IL-1β), and IL-6 (Zhou et al, 2018;Du et al, 2019; Figure 3). Furthermore, SY can inhibit the activation of the NF-κB signaling pathway by suppressing IκBα phosphorylation and cell nucleus translocation of p65 (Li et al, 2013; Figure 3).…”
Section: Safflower Yellow Inhibits the Hmgb1-tlr4-nf-κb Signaling Pathwaymentioning
confidence: 99%
“…Exposing neutrophils or macrophages to HMGB1 can lead to enhanced NF-κB signaling pathway and pro-inflammatory cytokine expression (Park et al, 2004). Interestingly, SY can improve inflammatory response and exert effect on inflammatory factors, like TNF-α, IL-1(IL-1β), and IL-6 (Zhou et al, 2018;Du et al, 2019; Figure 3). Furthermore, SY can inhibit the activation of the NF-κB signaling pathway by suppressing IκBα phosphorylation and cell nucleus translocation of p65 (Li et al, 2013; Figure 3).…”
Section: Safflower Yellow Inhibits the Hmgb1-tlr4-nf-κb Signaling Pathwaymentioning
confidence: 99%
“…Safflower is an extract of Crocus sativus L. and is commonly used in the treatment of CVD. Clinical studies have shown that safflower has antioxidant and antiarrhythmic effects, as well as protective effects on damaged myocardium [ 152 154 ]. Thus, safflower is an antioxidant with potential for the prevention and treatment of heart failure.…”
Section: Application Of Antioxidant Natural Drugs For Cardiovasculmentioning
confidence: 99%
“…In our study, we found that safflower yellow could dilate blood vessels, thereby lowering blood pressure, expanding coronary arteries, relieving myocardial ischaemia, and decreasing mental fatigue. This may be related to the fact that this drug can inhibit inflammation and oxidative stress, relieve pulmonary hypertension, reduce hypoxic pulmonary artery reconstruction, reverse right ventricular hypertrophy and remodelling, inhibit myocardial cell apoptosis, and improve cardiac ejection fraction [16, 17, 25], ultimately protecting and restoring cardiac function in patients with COPD and relieving heart palpitations and mental fatigue.…”
Section: Discussionmentioning
confidence: 99%